Alpha‐synuclein dynamics in induced pluripotent stem cell‐derived dopaminergic neurons from a Parkinson's disease patient (PARK4) with SNCA triplication. Issue 2 (5th January 2021) - Fukusumi, Hayato; Togo, Kazuyuki; Sumida, Miho; Nakamori, Masayuki; Obika, Satoshi; Baba, Kousuke; Shofuda, Tomoko; Ito, Daisuke; Okano, Hideyuki; Mochizuki, Hideki; Kanemura, Yonehiro
Abstract : Parkinson's disease (PD) is a neurodegenerative disorder caused by the selective loss of dopaminergic (DA) neurons in the substantia nigra pars compacta (SNc). Lewy bodies (LBs), another histological hallmark of PD, are observed in patients with familial or sporadic PD. The therapeutic potential of reducing the accumulation of α‐synuclein, a major LB component, has been investigated, but it remains unknown whether the formation of LBs results in the loss of DA neurons. PARK4 patients exhibit multiplication of the α‐synuclein gene ( SNCA ) without any pathological mutations, but their symptoms develop relatively early. Therefore, study of PARK4 might help elucidate the mechanism of α‐synuclein aggregation. In this study, we investigated the dynamics of α‐synuclein during the early stage of immature DA neurons, which were differentiated from human‐induced pluripotent stem cells (hiPSCs) derived from either a PARK4 patient with SNCA triplication or a healthy donor. We observed increased α‐synuclein accumulation in PARK4 hiPSC‐derived DA neurons relative to those derived from healthy donor hiPSCs. Interestingly, α‐synuclein accumulation disappeared over time in the PARK4 patient‐derived DA neurons. Moreover, an SNCA ‐specific antisense oligonucleotide could reduce α‐synuclein levels during the accumulation stage. These observations may help reveal the mechanisms that regulate α‐synuclein levels, which may consequently be useful in the development of new therapies for patients with sporadic or familial PD. Abstract : Alpha‐synuclein is a major component of Lewy bodies, which are a histological hallmark of Parkinson's disease (PD). In this study, we investigated the dynamics of α‐synuclein during the early stage of immature dopaminergic neurons differentiated from human‐induced pluripotent stem cells derived from either a PD patient with SNCA triplication or a healthy donor.